(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The media plays a significant role in our lives by informing us about the happenings across the world and shaping our opinions on various issues. In this context, different forms of media have distinct utility in the dissemination of news and other important information. Print media is one of the most powerful and omnipresent tools for spreading information to a vast number of people in a cost-effective manner. The impact of the written word has never been underestimated and it remains a strong medium of communication and conversation. It is worth noting that reading written information leaves a long-lasting and deep impact on individuals and helps guide their views on a subject. Therefore, print media is of great significance in conveying information to different sections of the society and understanding their opinions which, in turn, has an impact on policy making. This study is aimed at ascertaining and analysing the role of print media in spreading awareness on the issues of cleanliness and sanitation amongst the people of India. In this context, the study involves the analysis of news-related data of two leading national newspapers, namely ‘Dainik Bhaskar’ and ‘Rajasthan Patrika’. The overall levels of cleanliness in India are alarmingly low with minimal facilities for disposal of waste which is a major challenge for many people. Although there have been several programmes and campaigns drafted and launched by the government of India to improve the mechanisms of waste disposal and enhance the cleanliness levels across the country, the issue of waste management remains a persistent problem for most Indians. Furthermore, the research methodology adopted for the study is ’Content Analysis’ which is an appropriate technique to analyse the contents of national English dailys. The study is focused on assessing the level of importance that the aforementioned newspapers have assigned to news related to cleanliness and sanitation issues. In this context, the findings of the study have revealed that both the newspapers have provided due significance to the aforementioned issues in their news coverage.